The role of shelter in cherax abidus and bidyanus bidyanus polyculture systems - Wangpen, Prayadt (Curtin University, 2007)
Research into the polyculture of finfish and crayfish has been conducted in Western Australia for over a decade now. This research was instigated out of a need to increase revenues from freshwater crayfish farmers wishing to diversify their income base with a view to increasing profitability and reducing risk. It has become clear that several key variables dictate how the polyculture system (i.e. polysystem) will perform. These include biological factors like: size of participating species, relative densities, gender, planktonic turbidity, natural feeds; and abiotic factors like: light intensity, clay turbidity, floating cages for segregation, water quality, and habitat/shelter complexity. Many of these factors can be controlled / adjusted by the manager of the polysystem to maximise performance, production and profitability.While much of the research to date has focussed on the marron (Cherax tenuimanus) industry, it is also important to realise that an understanding of these factors can also assist other crayfish polysystems, like integrated agri-aquaculture systems containing yabbies (Cherax albidus). Some of the factors that influence how the system will perform may become more prevalent, like suspended clay turbidity and the associated role of light intensity in species interactions, or shelter complexity and the resulting choice of shelter material. But overall, they are the same basic variables and we must understand how they affect the particular multi-species system that we are dealing with. There is a lot to be learned from the literature on how these variables affect multi-species aquatic environments in the wild. Perhaps aquaculturists have not considered this enough in the past. Some farmers seem to believe that these variables are different JUST because it is a culture system. This is not true.The variables will take on different levels in a culture system (i.e. a manager will stimulate turbidity, provide artificial feeds, stock different sizes, and supply particular types of shelter) BUT the actual variables themselves (e.g. food, density, light, shelter) are basic to ALL aquatic ecosystems. Other researchers have looked at important factors like density, gender, and light intensity / turbidity in crayfish polysystems - but the issue of habitat complexity and the role of shelter has not been adequately addressed. This thesis will investigate some basic questions about shelter and endeavour to apply them to crayfish polysystems, with the emphasis on marron (C. tenuimanus) and yabbies (C. albidus) because these are the two most commercially important species of crayfish in Western Australia. Importantly, it should be noted that due to the invasive nature of yabbies, and their apparent ability to displace native marron in the wild, findings will be related to yabby-marron competition / displacement where relevant. We need to know many things about shelter: what type is best in a multi-species system? Should the shelter size match the crayfish size? Do marron have different requirements for shelter than yabbies? Does it matter who gets first use of a shelter (i.e. prior residence effect)? Can we learn about crayfish shelter requirements by examining the behaviour / plasticity of crayfish species? If crayfish are stocked with finfish and they retreat into shelter as a predator-avoidance measure, is the complexity important given that their densities will be higher? If densities of crayfish inside shelters are higher in polysystems, will cannibalism be a concern, particularly when conditions are right for moulting? Does visual recognition and / or chemo-detection of a predator affect the shelter usage by marron or yabbies?Does temperature affect shelter usage behaviour for a burrowing species like yabbies? Shelter is an important factor in the life history of a freshwater crayfish and an understanding of its influence on different species is important for maximising system performance. Crayfish are categorised depending on their ability to construct shelters (i.e. burrows). Yabbies have evolved in systems with fluctuating water quality and many predators and, as such, have learned to burrow (to escape drought and also to escape predators). Marron, on the other hand, are a non-burrowing native crayfish species that have existed with relatively few predators in the South-West. As a result, marron are less capable of modifying their behaviour when confronted with a predator (i.e. low behavioural plasticity). Species with high plasticity, like yabbies, are more capable of adapting to new environments, because they can change their behaviour to increase their chance of survival. Therefore we can expect yabbies and marron to utilize habitats differently and we should compare these behaviours as a basis to developing management strategies. This type of knowledge may also assist with managing the translocation and spread of yabbies in the wild and their displacement of native marron.Within multi-species systems, the physical structure of shelter plays an important role inprotecting crayfish and the perfect shelter would not only provide safety from co-stocked finfish, but also from conspecific cannibalism. Given the different life histories and behaviours, it is probable that both species of crayfish will have different refuge requirements.Over the course of this four-year investigation, trials were conducted in four culture systems (72L aquariums, 300L circular tanks, 80t mesocosm tank, and 720m2 earthen ponds) using marron and yabbies as the species of interest.Silver perch and Murray cod were chosen as the finfish species of interest as they appear to have the highest aquaculture potential for native freshwater finfish in Australia at the present time. Further, both of these fish have been documented as potential predators of crayfish, resulting in a challenge to understand the role of shelter in minimising the negative effects of fish-crayfish interactions within a polysystem. This study has confirmed that shelter plays a critical role in multi-species system dynamics. In the case of polysystems, it will affect both interspecific and intra-specific interactions, ultimately governing production and profitability, along with the other, previously defined factors. This means that the manager of a polysystem can influenceproductivity by understanding: a) the behavioural characteristics and biology of the crayfish; b) the feeding biology of the finfish; and c) the system variables (both biotic and abiotic) that will affect the overall well being of the fish and crayfish. In the case ofshelter, the manager should understand the available shelter types, the appropriatedensities, the importance of matching complexity to the crayfish size, and the prior residence effect when choosing a timing strategy for stocking and harvesting. Prior residence increased resource holding potential for both marron and yabbies in the short term. In fact, prior residence was a stronger determinant of successful sheltering than crayfish gender or species. However, in longer-term trials the physical size of the crayfish (larger animals evicted smaller animals) and reproductive status (berried females were successful at evicting all other crayfish) were more important factors in determining successful shelter acquisition, although the temporal variations (i.e. growth and release of young) complicate the issue.When stocking crayfish of different sizes, and in polysystems, the correct size of shelter becomes critical, as smaller individuals will be forced to leave over-sized shelter and locate a shelter commensurate with their own body size to avoid predators. This is relevant to crayfish nurseries where complex habitat is paramount for juvenile cohorts that display variation in sizes and gender. The expansion of crayfish polyculture holds considerable promise; however, furtherinvestigations are required into shelter complexity within floating fish cages, shelter types and arrangement of shelters within ponds (for increased production and ease-of-harvesting), potential of yabbies in polyculture (comparison of monosex and hybrid strains), and the impact of shelter on escape behaviour of marron in a polysystem.